Progetto di paesaggio arte e città (2013)
The aim of the research is to investigate how the set of artistic practices known as public art can create an area of co-design between landscape architecture, urban design and urban art. In recent years, art in the public space has gradually expanded from a conventional idea of monument to the idea of a sign contributing to urban regeneration: a sign building identity, a space creating relationships and relational processes. The research therefore aims to reflect and interpret the concepts that go in this direction, in the possibility of promoting their evolution that tends towards the definition of art, or rather the artistic act, not as an element of the urban scene, but as a process aimed at promoting a multidisciplinary dialogue. Art in/for/with the urban landscape can be read as a tool, as one of the possible means that can activate design processes.